2014
DOI: 10.1158/1078-0432.ccr-13-3396
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genetic Approach Identifies MET, HER3, IGF1R, INSR Pathways as Determinants of Lapatinib Unresponsiveness in HER2-Positive Gastric Cancer

Abstract: Purpose: Targeting human epidermal growth factor receptor 2 (HER2) therapy is currently considered as the standard treatment for HER2-positive (HER2 IntroductionPrevious studies have demonstrated that the human epidermal growth factor receptor 2 (HER2) signaling pathway is a critical driver of carcinogenesis and tumor progression in approximately 7% to 34% of total patients with gastric cancer (1-3). Targeting HER2 combined with chemotherapy has been the first-line treatment for HER2-positive (HER2 þ ) advanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 35 publications
3
70
0
Order By: Relevance
“…However, some reports have shown that loss of PTEN expression or deletion of the PTEN gene is rarely found (3.7-5.3 %) in HER2-overexpressing gastric cancer [23,24]. The discrepancy in these results might be due to variations in the definition of PTEN loss.…”
Section: Discussionmentioning
confidence: 96%
“…However, some reports have shown that loss of PTEN expression or deletion of the PTEN gene is rarely found (3.7-5.3 %) in HER2-overexpressing gastric cancer [23,24]. The discrepancy in these results might be due to variations in the definition of PTEN loss.…”
Section: Discussionmentioning
confidence: 96%
“…S3A). Next, a Cre-inducible allele of the MET receptor tyrosine kinase, which is associated with EMT and therapy resistance (18,19), and expressed at high levels in breast cancer (20)(21)(22), was introduced in KB1P-Col1a1 ESC clone A2.1 to produce K14cre;Brca1 F/F ; Trp53 F/F ;Col1a1 inv-CAG-Met-Luc (KB1P-MET) ESCs (Fig. S3B).…”
Section: Met Accelerates Mammary Tumor Development In Kb1p Chimericmentioning
confidence: 99%
“…IGF1R has been suggested to play a role in ovarian cancer due to its upregulation after combined PI3K and mTOR inhibition (43) as well as in a range of ovarian cancer cell lines after AKT inhibition (20), but was not pursued with functional inhibitor experiments in these studies. These and other (44)(45)(46)(47) examples demonstrate that IGF1R inhibition may prove a valuable addition to inhibitors targeting the MAPK and PI3K pathways.…”
Section: Discussionmentioning
confidence: 88%